Flexural strength of concrete beam by using wood block as aggregate replacement - Nur Affini, Azmi (2019)
Nowadays, the demand for the concrete industry is raising consequent with the developing of new house property. The effect of the property industry may cause of demand in natural aggregate. It will issue to the all quarries industry to fulfil the market demand. Thus, alternative to deal with market demand by replacing the natural coarse aggregate with the waste wood block from factory. The study was conducted by using wood block as replacement of coarse aggregate. The study was involved by produce the beam size 150 mm x 200 mm x 1500 mm and cube specimen size 150 mm x 150 mm x 150 mm. The specimen was casting with different percentage of wood block replacement which is 3% and 6%. For the precaution, wood block was paint at the surface area to avoid water absorption. The test was carrying out for cube specimen was a compressive strength and for the beam was flexural test. By comparing the performance of the compressive strength for replacing 3% and 6% of wood block, it can be conclude to use 6% as a replacement for coarse aggregates based on the average compressive strength for 7 days which is 23.24 N/mm2.